Employing Financial Futures to Increase the Return on Near Cash (Treasury Bill) Investments - Elton, Edwin J.; Gruber, Martin J.; Rentzler, Joel C. (Management Science, 1985)
The purpose of this article is to formulate and test a decision model to increase the return on a pool of liquid assets through the use of Treasury bill futures contracts. Recent literature has documented inefficiencies in the pricing of T-bill futures. These inefficiencies can be exploited to increase the return on a portfolio of T-bills without affecting the maturity of the portfolio. The solution technique used is dynamic programming. The results of applying a dynamic programming algorithm parameterized on available data to trade in real time are presented. The rules lead to increased returns.